2019
DOI: 10.32637/orli.v34i4.293
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of Dysphagia with Fiberoptic Endoscopic Examination of Swallowing (FESS) and its Future Implementation in Indonesia

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The severity of the disease on the admission of the research subject will certainly affect the findings on FEES. 13 Based on our results, there was no significant difference between the two groups related to hypopharyngeal sensitivity in FEES. Nayoan 16 study of 28 samples found that 14 patients (50%) had hypopharyngeal hyposensitivity.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The severity of the disease on the admission of the research subject will certainly affect the findings on FEES. 13 Based on our results, there was no significant difference between the two groups related to hypopharyngeal sensitivity in FEES. Nayoan 16 study of 28 samples found that 14 patients (50%) had hypopharyngeal hyposensitivity.…”
Section: Discussionmentioning
confidence: 57%
“…In neurogenic dysphagia (post stroke/head trauma), leakage occurs due to impairment on glossopharyngeal (n.XI), which carries sensory components or on n. hypoglossal (n. XII), which carries motoric components. 2,6,13,21 This study found that residual dysphagia occurred more frequently in non-neurogenic dysphagia than neurogenic dysphagia. Iqbal et al 14 in 2014 stated that water residue was 16 times greater in neurogenic dysphagia than in mechanical dysphagia.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations